2013
DOI: 10.2188/jea.je20120101
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Protein, Fat, and Carbohydrate Intakes With Insomnia Symptoms Among Middle-aged Japanese Workers

Abstract: BackgroundDiet is a modifiable factor that may affect sleep, but the associations of macronutrient intakes with insomnia are inconsistent. We investigated the associations of protein, fat, and carbohydrate intakes with insomnia symptoms.MethodsIn this cross-sectional analysis of 4435 non-shift workers, macronutrient intakes were assessed by the brief-type self-administered diet history questionnaire, which requires the recall of usual intakes of 58 foods during the preceding month. Presence of insomnia symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
82
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 38 publications
(40 reference statements)
4
82
2
4
Order By: Relevance
“…Regarding macronutrients, a study of Japanese workers showed a marginally significant association between low carbohydrate intake and difficulty in maintaining sleep 14) , and our results for carbohydrate were inconsistent with this paper. On the other hand, there are other past studies showing opposite results that were consistent with ours 29) .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding macronutrients, a study of Japanese workers showed a marginally significant association between low carbohydrate intake and difficulty in maintaining sleep 14) , and our results for carbohydrate were inconsistent with this paper. On the other hand, there are other past studies showing opposite results that were consistent with ours 29) .…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, altering dietary habits is more feasible than altering lifestyle behaviors in female workers. Evidence supporting the relationship between sleep quality and diet has been scarce, however, and of those available, two studies, one each from Japan 14) and the US 15) , utilized non-validated questionnaires. The relationship between dietary intake and sleep quality would be better understood by studies utilizing validated questionnaires.…”
mentioning
confidence: 99%
“…Other epidemiologic studies have found associations between disordered sleep and diet (16)(17)(18). Tanaka et al (16) reported a relation between macronutrient intakes and insomnia symptoms in a cross-sectional analysis of non-shift workers who responded to a brief diet history questionnaire.…”
Section: Dietary Patterns and Sleep Qualitymentioning
confidence: 99%
“…Tanaka et al (16) reported a relation between macronutrient intakes and insomnia symptoms in a cross-sectional analysis of non-shift workers who responded to a brief diet history questionnaire. Low protein intake (<16% of energy from protein) was associated with poor quality of sleep and marginally associated with difficulty initiating sleep, whereas high protein intake (>19% of energy from protein) was associated with difficulty maintaining sleep.…”
Section: Dietary Patterns and Sleep Qualitymentioning
confidence: 99%
See 1 more Smart Citation